(untitled) (Indonesian Journal of Counseling and Development, 2021)
The study aims to uncover a self-esteem relationship with the altruistic motivations of students who participate in scouting activities. This research method uses a quantitative approach with a correlational descriptive method with a population of 104 people who come from students of State Junior High School 7 Sungai Penuh who participated in Scout activities, then samples were taken using a simple random sampling formula then obtained a sample of 83 people. The tool reveals self-esteem data in an adaptation of the Coopersmith Self-Esteem Inventory (CSEI) and the altruistic motivation data researchers developed themselves, namely the Altruistic Motivation Scale (SMAL). The data of the study results were processed and analyzed descriptively to see the distribution of frequencies and then conducted a correlation test using Pearson Product Moment Correlation. The results of this study revealed that the self-esteem and altruistic motivation of students who participated in scouting activities in school were on average in the world